Corticotropin‐releasing factor infusion into nucleus incertus suppresses medial prefrontal cortical activity and hippocampo‐medial prefrontal cortical long‐term potentiation. Issue 4 (14th May 2013) - Farooq, Usman; Rajkumar, Ramamoorthy; Sukumaran, Shalini; Wu, You; Tan, Wei Hao; Dawe, Gavin Stewart
Abstract The medial prefrontal cortex (mPFC) in the rat has been implicated in a variety of cognitive processes, including working memory and expression of fear memory. We investigated the inputs from a brain stem nucleus, the nucleus incertus (NI), to the prelimbic area of the mPFC. This nucleus strongly expresses corticotropin‐releasing factor type 1 (CRF1) receptors and responds to stress. A retrograde tracer was used to verify connections from the NI to the mPFC. Retrogradely labelled cells in the NI expressed CRF receptors. Electrophysiological manipulation of the NI revealed that stimulation of the NI inhibited spontaneous neuronal firing in the mPFC. Similarly, CRF infusion into the NI, in order to mimic a stressful condition, inhibited neuronal firing and burst firing in the mPFC. The effect of concurrent high‐frequency stimulation of the NI on plasticity in the hippocampo‐prelimbic medial prefrontal cortical (HP‐mPFC) pathway was studied. It was found that electrical stimulation of the NI impaired long‐term potentiation in the HP‐mPFC pathway. Furthermore, CRF infusion into the NI produced similar results. These findings might account for some of the extra‐pituitary functions of CRF and indicate that the NI may play a role in stress‐driven modulation of working memory and possibly other cognitive processes subserved by the mPFC.